Are two halves better than one whole? A comparison of the amount and quality of sleep obtained by healthy adult males living on split and consolidated sleep–wake schedules. (February 2017) - Roach, Gregory D.; Zhou, Xuan; Darwent, David; Kosmadopoulos, Anastasi; Dawson, Drew; Sargent, Charli
Abstract: The aim of this study was to compare the quantity/quality of sleep obtained by people living on split and consolidated sleep–wake schedules. The study had a between-groups design, with 13 participants in a consolidated condition (all males, mean age of 22.5 yr) and 16 participants in a split condition (all males, mean age of 22.6 yr). Both conditions employed forced desynchrony protocols with the activity:rest ratio set at 2:1, but the consolidated condition had one sleep–wake cycle every 28 h (9.33 + 18.67), while the split condition had one sleep–wake cycle every 14 h (4.67 + 9.33). Sleep was assessed using polysomnography. Participants in the split and consolidated conditions obtained 4.0 h of sleep per 14 h and 7.6 h of sleep per 28 h, respectively. Some differences between the groups indicated that sleep quality was lower in the split condition than the consolidated condition: the split sleeps had longer sleep onset latency (9.7 vs. 4.3 min), more arousals (7.4 vs. 5.7 per hour in bed), and a greater percentage of stage 1 sleep (4.1% vs. 3.1%), than the consolidated sleeps. Other differences between the groups indicated that sleep quality was higher in the split condition than the consolidated condition: the split sleeps had a lower percentage of wake after sleep onset sleep (11.7% vs. 17.6%), and a greater percentage of slow wave sleep (30.2% vs. 23.8%), than the consolidated sleeps. These results indicate that the split schedule was not particularly harmful, and may have actually been beneficial, to sleep. Split work–rest schedules can be socially disruptive, but their use may be warranted in work settings where shiftworkers are separated from their normal family/social lives (e.g., fly-in fly-out mining) or where the need for family/social time is secondary to the task (e.g., emergency response to natural disasters).